Complexity Compression in Rural Nursing - Maura Conaty Schlairet (Rural Nurse Organization; Binghamton University, 2017)
A large and increasing body of literature suggests nurses face mounting production pressure related to complexity of patients, systems, and escalating demands from both. This phenomenon is identified as complexity compression and describes an experience wherein nurses are expected to take on additional, unplanned responsibilities while simultaneously satisfying existing responsibilities in a condensed timeframe. Rural nursing practice appears as a fitting example of doing more and doing differently in a time-pressured environment. However, the phenomenon of complexity compression has yet to be discussed specifically in relation to rural nursing or from the lens of a rural nursing theory. Conceptualization of complexity compression in rural nursing through use of theory may help redefine the true nature of rural nursing practice and promote discussion and collaboration among nurses, administrators, educators, and policy makers in creation of better rural work environments, improved educational opportunities for rural nurses, and robust healthcare outcomes for rural populations. Keywords: Complexity Compression, Conceptualization, Theory, Rural Nursing DOI: http://dx.doi.org/10.14574/ojrnhc.v17i2.445